Mitigating Heat Wave and Exposure Damage to “Cabernet Sauvignon” Wine Grape With Partial Shading Under Two Irrigation Amounts - Martínez-Lüscher, Johann; Chen, Christopher Cody Lee; Brillante, Luca; Kurtural, Sahap Kaan (Frontiers in Plant Science, 2020)
Rising temperatures in most agricultural regions of the world are associated with a higher incidence of extreme weather events such as heat waves. We performed an experiment to mitigate the impact of heat waves and exposure of berries in grapevine (Vitis vinifera cv. ‘Cabernet Sauvignon’) with untreated vines (Exposed) or with fruit-zone partial shading (Shaded) under 40% and 80% replacement of crop evapotranspiration (ETc) with sustained deficit irrigation in a factorially arranged experiment. The trial was performed in a vineyard with vertically shoot positioned trellis with a row orientation that concentrated solar radiation exposure on the southwest aspect of the fruit zone. Leaf stomatal conductance (gs) and net carbon assimilation (AN) were significantly lower in shaded leaves under partial fruit-zone shading that resulted in lower pruning mass for Shaded treatments. Stem water potential (Ψstem) responded to a large extent to increased irrigation. However, grapevines with partial fruit-zone shading had transiently better water status under 40% ETc. Cluster maximum temperatures were 3.9 oC greater in Exposed grapevines. Exposed clusters had transiently lower acidity and higher pH. However, Exposed clusters on 40% ETc had higher total soluble solids (TSS). The experimental vineyard suffered a 4-day heat wave 21 days before harvest, resulting in 25% of the clusters being damaged in Exposed treatment, regardless of irrigation amount. Furthermore, berries in Exposed treatments suffered a great loss of anthocyanins and flavonols even if they were not damaged by direct solar exposure. The pre-planting decision of using a vertically shoot positioned trellis that concentrated solar radiation on the Southwest aspect offered mild protection in a hot climate region with a sunny growing season with extreme heat events during the execution of study. The extreme conditions under which this study was conducted are not unusual, and have become more expected. Our work provided evidence of the vulnerability of grape berry to heat waves and exposure during heat wave events and possible protection methods to mitigate these effects in situ in context of climate change.